Overview of the Level of Activity Daily Living of the elderly who have chronic diseases in the Geriatric Polyclinic of the State General Hospital - Ni Wayan Suetri; Sang Ayu Ketut Candrawati; Ni Ketut Citrawati (Professional Health Journal)
Introduction: The increase in the elderly population will of course be accompanied by an increase in the risk of suffering from chronic diseases which can accelerate functional decline and reduce the ability of the elderly to carry out important activities in daily living Activities of Daily Living (ADL